PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVA SDN 67 PEMATANG PUDU KECAMATANMANDAU KABUPATEN BENGKALIS - Yanti, Erlina; Antosa, Zariul; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract. Kooperatif tipe teached is a made tipe koopeated teached used a small team with four peaple for a team that contain of intelegency, jender, and etnic. This research was carried out because of low learning outcomes IPA A fourth grade students of SD Negeri 67 Pematang Pudu . Of the 28 students who reached the KKM as many as 11 students ( 39.29 % ) while students who did not complete 17 students ( 60.71 % ) with an average of 60.71 . The purpose of this research to improve learning outcomes IPA A fourth grade students of SD Negeri 67 Pematang Pudu with learning model application Student Teams Achievement Divisions ( STAD ). The results obtained by the average value of 60.71 basic score increased in the first cycle of 35.71 % to 70.71 . In the second cycle the average value of students also increased by 17.86 % to 78.75 . On the basis of completeness score IPA student learning outcomes is only 39.29 % ( complete) . Once applied learning model teacher Students Teams Achievement Divisions ( STAD ) in the first cycle classical completeness increased to 75 % ( complete) . In the second cycle completeness klsaikal obtained are increased increased to 92.86 % ( complete) .Key Words: Student Teams Achievement Divisions, Learning Outcomes, IPA